2020
DOI: 10.1021/acs.jpcb.0c01566
|View full text |Cite
|
Sign up to set email alerts
|

Liquid/Vapor Interface of Dimethyl Carbonate–Methanol Binary Mixtures Investigated by Sum Frequency Generation Vibrational Spectroscopy and Molecular Dynamics Simulation

Abstract: In the present work, the dimethyl carbonate (DMC)−methanol binary mixture was used as a benchmark system to study the molecular structures of the liquid/vapor interface of organic−organic mixtures by sum frequency generation vibrational spectroscopy (SFG-VS) and molecular dynamics (MD) simulations. It was discovered that both the methanol and DMC molecules are anisotropically oriented at the surface, yielding strong SFG-VS signals in the C−H stretching frequency range for both molecules. The detailed analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…Such ρ< cosθ μ > profiles could help us to compare the MD results with the SFG-VS results for the molecules with broken centrosymmetry will contribute to the SFG-VS signal. 34,52,53 The ρ and ρ< cosθ μ >profiles for x but = 0.10 to 0.59 are plotted in Figure S9 (SI). The enrichment of BUT molecules can be observed in the transition regions for these mixtures.…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…Such ρ< cosθ μ > profiles could help us to compare the MD results with the SFG-VS results for the molecules with broken centrosymmetry will contribute to the SFG-VS signal. 34,52,53 The ρ and ρ< cosθ μ >profiles for x but = 0.10 to 0.59 are plotted in Figure S9 (SI). The enrichment of BUT molecules can be observed in the transition regions for these mixtures.…”
Section: 3mentioning
confidence: 99%
“…54 On the basis of the current work and our previous study on vapor/liquid interface of dimethyl carbonate and methanol binary mixture, we proved that the orientation of the interfacial molecules were not directly relevant to the mole fraction of the azeotrope at a room temperature. 34 But a higher temperature compared to the ambient environment might lead to an orientation change of the interfacial molecules. Besides it has to be mentioned that the mechanism of the narrow decline in the intensity of SFG-VS spectra during the temperature rise around the azeotropic mole fraction is still not clear.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular energetics analysis shows that these free energy changes are mainly due to energy interactions, especially selfinteractions between homologous molecules. Hou et al 38 studied the molecular structure of the liquid/vapor interface of DMC-methanol mixture by using sum frequency generation vibrational spectroscopy (SFG-VS) and MD simulation. It was found that both methanol and DMC molecules are anisotropic in surface orientation, and the increase of methanol concentration can significantly decrease the orientation order of methyl groups in DMC and methanol molecules at the interface, but does not significantly affect the orientation of carbonyl groups in DMC.…”
Section: Molecular Simulation Of the Formation Mechanism Of Azeotropementioning
confidence: 99%
“…The low density of interfacial molecules poses a challenge to probe them. In this regard, molecular dynamics (MD) simulations have proven to be very useful in understanding the arrangement of molecules therein. , The combined application of MD simulations and surface spectroscopic techniques has facilitated the comprehensive understanding of interfacial structure at the atomic level. ,, The l–v interface of aqueous solutions of many organic solvents, such as acetonitrile, dimethylformamide (DMF), dimethyl sulfoxide , (DMSO), formic acid, ,, ethanol, , methanol (MeOH), ,, etc., has been extensively investigated in the literature. These organic molecules are preferentially adsorbed at the interface due to their amphiphilic nature.…”
Section: Introductionmentioning
confidence: 99%